(INTER)NATIONALISATION AT HOME: A GEOSEMIOTIC ANALYSIS OF THE BILINGUAL LINGUISTIC SCHOOLSCAPE OF A PRIVATE ISLAMIC-BASED NATIONAL UNIVERSITY IN YOGYAKARTA, INDONESIA - Sadiq, Nizamuddin (Masyarakat Linguistik Indonesia, 2024)
This paper focuses on the linguistic schoolscape within the confines of a private Islamic university located in Yogyakarta, Indonesia. Employing a geosemiotic approach, the study integrates two distinct dimensions, namely visual semiotics and place semiotics, with the aim of elucidating the nuanced social meanings inherent in the linguistic environment of the university. Drawing upon a meticulous analysis of 200 distinct signs, it is revealed that the prevailing linguistic expression encompasses monolingual Indonesian discourse, accounting for 61% of the corpus, alongside a significant presence of bilingual English-Indonesian discourse, constituting 34.7% of the top-down category. Conversely, within the bottom-up category, monolingual Indonesian discourse maintains dominance at 69.9%, followed by bilingual Indonesian-English discourse at 13.7%. This study discerns two principal dimensions within the realm of visual semiotics: pictorial representations and material attributes. Pictures representations predominantly manifest as compositions of images, texts, or a fusion thereof. Material aspects encompass considerations of code preference, inscription modalities, and spatial emplacement. At this university, code preference reflects a nuanced interplay among various linguistic statuses, notably including the presence of Javanese (a local language), Indonesian, and English, with monolingual Indonesian holding a position of prestige alongside bilingual English-Indonesian or Indonesian-English expressions. Inscriptions typically adopt screen printing techniques, employ small font sizes, and exhibit compact board dimensions, characterised by a horizontal orientation and white colouring. Emplacement practices entail the strategic positioning of signage along thoroughfares and occasionally include instances of transgressive signage. In the domain of place semiotics, it is discerned that the perceptual space within which signs operate is inherently interconnected with the surrounding built environment and spatial configurations. This symbiotic relationship between signs and their spatial context engenders a cohesive visual landscape. Pertaining to the utilisation of space, institutional signage predominates in top-down configurations, while signage displays in bottom-up arrangements play a significant role in delineating functional spaces.